Network alarm monitoring system-temperature in server room - NorfidaErwani, Mohd Shafie (2005)
Together with the rapid growth in information technology (IT), server is important instruments that need in every company even the small company indeed.Network Alarm Monitoring System - Temperature in Server Room is a project to develop a prototype that capable to keep those server investments in a good condition,providing a return and help keep downtime to a minimum. This is because server is computer equipment that is so sensitive and need a fully care every time. So for security, the system development need to trigger an alarm sound as a warning sign if the temperature is go off from the setting range. This is the most valuable asset because the risk for losing the important data can be avoided especially when network administrator was in incautious situation. The techniques that used for developing this project prototype are combine skills in development software and hardware where a circuit that capable to detect the level of temperature is developed. For the temperature sensor,LM35dz thermometer-in chip is used as the main chip for this project. A part of the warning sound, in the same time one (1) of the three (3) LED also take turn to light on based on the current temperature condition and status. In shortly, red LED is light on if the server room temperature was exceeded from the setting range, green LED is used for the normal temperature while yellow LED is function as the warning sign for lower temperature. Then an interface to display the current temperature value and status is developed by using Visual Basic version 6.0 applications.